Carbohydrate-rich supplements can improve nitrogen use efficiency and mitigate nitrogenous gas emissions from the excreta of dairy cows grazing temperate grass. (7th June 2020) - Almeida, J. G. R.; Dall-Orsoletta, A. C.; Oziemblowski, M. M.; Michelon, G. M.; Bayer, C.; Edouard, N.; Ribeiro-Filho, H. M. N.
Abstract : Temperate pasture species constitute a source of protein for dairy cattle. On the other hand, from an environmental perspective, their high N content can increase N excretion and nitrogenous gas emissions by livestock. This work explores the effect of energy supplementation on N use efficiency (NUE ) and nitrogenous gas emissions from the excreta of dairy cows grazing a pasture of oat and ryegrass. The study was divided into two experiments: an evaluation of NUE in grazing dairy cows, and an evaluation of N-NH3 and N-N2 O volatilizations from dairy cow excreta. In the first experiment, 12 lactating Holstein × Jersey F1 cows were allocated to a double 3 × 3 Latin square (three experimental periods of 17 days each) and subjected to three treatments: cows without supplementation (WS ), cows supplemented at 4.2 kg DM of corn silage (CS ) per day, and cows supplemented at 3.6 kg DM of ground corn (GC ) per day. In the second experiment, samples of excreta were collected from the cows distributed among the treatments. Aliquots of dung and urine of each treatment plus one blank (control – no excreta) were allotted to a randomized block design to evaluate N-NH3 and N-N2 O volatilization. Measurements were performed until day 25 for N-NH3 and until day 94 for N-N2 O. Dietary N content in the supplemented cows was reduced by 20% ( P < 0.001) compared with WS cows, regardless of the supplement. Corn silage cows had lower N intake ( P < 0.001) than WS and GC cows (366 v. 426 g/day, respectively). Ground corn supplementation allowed cows to partition more N towards milk protein compared with the average milk protein of WS cows or those supplemented with corn silage (117 v. 108 g/day, respectively; P < 0.01). Thus, even though they were in different forms, both supplements were able to increase ( P < 0.01) NUE from 27% in WS cows to 32% in supplemented cows. Supplementation was also effective in reducing N excretion (761 v. 694 g/kg of Nintake ; P < 0.001), N-NH3 emission (478 v. 374 g/kg of Nmilk ; P < 0.01) and N-N2 O emission (11 v. 8 g/kg of Nmilk ; P < 0.001). Corn silage and ground corn can be strategically used as feed supplements to improve NUE, and they have the potential to mitigate N-NH3 and N-N2 O emissions from the excreta of dairy cows grazing high-protein pastures.